Pufa content in selected organ for several species of sharkin Terengganu water - Fahrudin Umar (Terengganu: Universiti Malaysia Terengganu, 2014)
This research was carried to determine the PUFA content of different species of shark in different major organ. Three species of sharks was utilized in this research, namely Carcharhinus limbatus (black-tip shark), Carcharhinus sealei (silvery shark) and Carcharhinus dussumieri (wide-mouthed black spot shark).